2017
DOI: 10.1590/1678-4324-2017160352
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of a MYB Protein from Oryza sativa for its Role in Abiotic Stress Tolerance

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…This MYB was one of the first discovered in apple and was also named MYB1, which has created confusion in the literature. It is most similar to the Arabidopsis MYB1 (in a clade with AtMYB109, ATMYB25, and OsMYB1), which has been shown to be upregulated in response to abiotic stresses (Deeba et al, 2017). The commercial grower reported that irrigation was turned off in the experimental orchard 4 weeks before the final samples were collected, so it is possible that the increased expression for this apple MYB was due to water stress and/or heat stress.…”
Section: Resultsmentioning
confidence: 99%
“…This MYB was one of the first discovered in apple and was also named MYB1, which has created confusion in the literature. It is most similar to the Arabidopsis MYB1 (in a clade with AtMYB109, ATMYB25, and OsMYB1), which has been shown to be upregulated in response to abiotic stresses (Deeba et al, 2017). The commercial grower reported that irrigation was turned off in the experimental orchard 4 weeks before the final samples were collected, so it is possible that the increased expression for this apple MYB was due to water stress and/or heat stress.…”
Section: Resultsmentioning
confidence: 99%
“…Like in tomato, overexpression of LeAN2 improved the resistance of plants against heat stress through a high level of antioxidants activity (non-enzymatic) and a low level of ROS accumulation [103]. In rice, overexpressing OsMYB1 gene can increase the tolerance of plants to both heat and salinity stresses [104]. While in maize, OsMYB55 proved to be effective in enhancing tolerance against high temperature and drought stress with improved growth and development of seedlings [105].…”
Section: Function and Expression Pattern Of Myb Tfs Under Abiotic Strmentioning
confidence: 99%
“…Similarly, the beneficial effect of different members of the WRKY gene family under excess water stress was also documented for Arabidopsis, sunflower, and other crops (Hsu et al 2013;Raineri et al 2015;Han et al 2019). In rice, an R2-R3 type MYB transcription factor (OsMYB1) is reported to be associated with waterlogging tolerance (Deeba et al 2017) and ROS scavenging (Yokotani et al 2013).…”
Section: Discussionmentioning
confidence: 90%